2018
DOI: 10.1530/erc-18-0097
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts and challenges to unravel the role of iodothyronine deiodinases in human neoplasias

Abstract: Thyroid hormones (THs) are essential for the regulation of several metabolic processes and the energy consumption of the organism. Their action is exerted primarily through interaction with nuclear receptors controlling the transcription of thyroid hormone-responsive genes. Proper regulation of TH levels in different tissues is extremely important for the equilibrium between normal cellular proliferation and differentiation. The iodothyronine deiodinases types 1, 2 and 3 are key enzymes that perform activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 191 publications
3
15
0
Order By: Relevance
“…We found significant upregulation of DIO2 mRNA levels in primary tumor tissues of colon cancer as compared with the normal colon tissue (Figure A). The result is consistent with data provided in a recent review . Rectal cancer gene expression data also showed upregulation of DIO2 mRNA in primary rectal tumor tissues (Figure A) as compared with the normal rectal tissue.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We found significant upregulation of DIO2 mRNA levels in primary tumor tissues of colon cancer as compared with the normal colon tissue (Figure A). The result is consistent with data provided in a recent review . Rectal cancer gene expression data also showed upregulation of DIO2 mRNA in primary rectal tumor tissues (Figure A) as compared with the normal rectal tissue.…”
Section: Resultssupporting
confidence: 91%
“…Although altered expression of DIO2 has been reported in other types of malignancies, including brain tumors and thyroid cancer, the role of stromal DIO2 in tumor angiogenesis has not been documented so far. Thyroid hormone signaling itself, however, has been implicated in tumor angiogenesis through binding of the prohormone T4 to integrin αvβ3 on the surface of endothelial and vascular smooth muscle cells .…”
Section: Discussionmentioning
confidence: 99%
“…Some data indeed suggest that T3 can contribute to tumor growth in breast cancer cells in vitro 17 , while a microenvironment with low T3 levels could facilitate invasiveness and dedifferentiation. However, in agreement with our data in breast cancer, similar levels of DIO3 mRNA are observed in glioblastoma and liver carcinomas as compared to respective normal tissues 45 . These differences could be attributed to the tissue embryological origin since the tissues of ectodermal origin seem to maintain DIO3 expression during adulthood, while DIO3 gene is subject to imprinting in other tissues.…”
Section: Discussionsupporting
confidence: 93%
“…18 TCGA data analysis has shown that DIO2 expression is upregulated in breast cancers compared to normal tissue. 9 DIO3 express highly during embryonic development and cancer. Immortalized cell line in different tumours such as breast, colon, thyroid, and neuroblastoma express elevated D3 levels.…”
Section: Deiodinases Er Status Casesmentioning
confidence: 99%
“…8 Oncogenesis is effected by deregulation of bio availability of TH at cellular levels that critically determined by the enzymatic activity of deiodinases. 9 Therefore, we perform an analyzed the prognostic role of DIO1-3 in human breast cancer patient by Kaplan Meier plotter (KM plotter). We accessed KM plotter for the analysis of NIS and deiodinase with clinical results calculating relapse-free survival (RFS) and hazard ratio (HR).…”
Section: Introductionmentioning
confidence: 99%